(untitled) (International Journal of Scientific Trends, 2025)
This article is based on the fact that the development of information technologies, nanotechnologies, biotechnology, cognitive technologies, automation and rabotization of production, digitization and robotizatsion of production, digitizatsion and cybernetcization of management are placing new professional and requirements on the trends in the dynamics of demand for professions, the decrease in demand for some popular proffessions, and the increase in demand for some new professions.